2021
DOI: 10.3390/ijerph18041779
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tobacco Use Patterns during COVID-19 and Their Correlates among Older Adults in Bangladesh

Abstract: The present study explored the changes in tobacco use patterns during the COVID-19 pandemic and their correlates among older adults in Bangladesh. This cross-sectional study was conducted among 1032 older adults aged ≥60 years in Bangladesh through telephone interviews in October 2020. Participants’ characteristics and COVID-19-related information were gathered using a pretested semi-structured questionnaire. Participants were asked if they noted any change in their tobacco use patterns (smoking or smokeless t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
5
22
4
1
Order By: Relevance
“…Most participants reported an increased consumption or reduced consumption. Increased tobacco use during the pandemic has been also reported in recent studies [39,41,46]. Besides, many current smokers in our study have reported their intention to quit smoking during the pandemic, which was also one of the findings of various studies during the pandemic crisis [37,41].…”
Section: Discussionsupporting
confidence: 86%
“…Most participants reported an increased consumption or reduced consumption. Increased tobacco use during the pandemic has been also reported in recent studies [39,41,46]. Besides, many current smokers in our study have reported their intention to quit smoking during the pandemic, which was also one of the findings of various studies during the pandemic crisis [37,41].…”
Section: Discussionsupporting
confidence: 86%
“…Most participants reported an increased consumption or reduced consumption. Increased tobacco use during the pandemic has been also reported in recent studies (40,43,45). Besides, many current smokers in our study have reported their intention to quit smoking during the pandemic, which was also one of the ndings of various studies during the pandemic crisis (37,45).…”
Section: Discussionsupporting
confidence: 82%
“…A structured questionnaire was developed by the authors after reviewing relevant and related literature (19,35,37,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The questionnaire comprised 39 single-answer items that were distributed over three sections as the following:…”
Section: Assessment Tool and Measuresmentioning
confidence: 99%
“…Another limitation was that the study used existing chart data without obtaining participant information regarding motives for changing their tobacco use patterns, and whether they were COVID-related. This limitation prevents us from drawing firm conclusions about why participants' tobacco use patterns changed during the peak of the pandemic (as was done in survey studies during the early pandemic [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]).…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons for decreased tobacco use were perceptions of greater risks of both becoming infected and suffering severe complications due to COVID-19, along with more time spent around non-users [18]. While the majority of studies suggest that tobacco use rates stayed the same during the initial stages of the pandemic, some studies did show that overall rates either increased [19][20][21] or decreased [22][23][24][25]. Taken together, these studies demonstrate that overall tobacco use rates remained largely unchanged during the early stages of the pandemic, at least in the populations cited above.…”
Section: Introductionmentioning
confidence: 99%